Foreign direct investment and its impact on industry in Kingdom of Saudi Arabia - Systematic Review - Nasrulddin, Vivian Mohammed Saleh; Al-Juaid, Bayan Khalaf; Al-Ghamdi, Kholoud Bakheet Misfer; Al-Idrisi, Tharaa Hassan Omar (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aims to review the literature on foreign direct investment and its impact on the industrial sector. In order to achieve the aim of the study, the methodology of the grounded theory in qualitative research was relied upon, by examining the related economic and scientific researches. The number of studies examined was (19) studies. After analyzing the results of the studies under examination, the current study concluded that there is a positive relationship between foreign investment and the industrial sector, so that an increase in foreign investment flows leads to an increase in the growth of the industrial sector in the KSA. The current study presented a number of recommendations, including the need to continue to encourage and attract foreign direct investments with directing them more to industrial sector projects, especially those that operate idle resources in which local capital cannot invest, in addition to emphasizing the need to take advantage of the technological knowledge coming with those investments. As well as the need to take advantage of the process of trade liberalization to increase national exports and reduce imports. The researchers also recommended the need to conduct similar studies on the impact of foreign direct investment on various economic sectors, such as the services and tourism sector, to which foreign direct investment is more attracted than the industrial sector.